2018
DOI: 10.7150/jca.22157
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics of the primary and metastatic Hepatic Neuroendocrine Tumors and the relevant Prognosis-Related Factors: A Retrospective Study of 81 Cases in a Single Chinese Center

Abstract: Aims: We aim to describe the clinicopathological characteristics of hepatic neuroendocrine tumors (HNETs) and evaluate the relevant prognosis-related factors.Methods: The clinical data of 81 consecutive patients with primary or metastatic HNETs from March 2000 to July 2014 were retrospectively analyzed.Results: The mean (SD) age was 59.68 (11.64) years, 69.15% were men. The percentages of Grade G1, G2 and G3 tumors were 4.94%, 25.93% and 69.13%, respectively. Thirty-five cases were primary HNETs. Primary HNETs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 22 publications
2
20
2
Order By: Relevance
“…( Table 1). This demography was much close to the reports by some previous studies [26,27] . In our study, 64 MH-NENs were secondary to pancreas (42.7%), 96 cases were diagnosed synchronously with the primary lesions (64%), 127 cases showed over 50% estimated liver involvement (84.7%) and 42 cases simultaneously present extrahepatic invasion at diagnosis (28%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…( Table 1). This demography was much close to the reports by some previous studies [26,27] . In our study, 64 MH-NENs were secondary to pancreas (42.7%), 96 cases were diagnosed synchronously with the primary lesions (64%), 127 cases showed over 50% estimated liver involvement (84.7%) and 42 cases simultaneously present extrahepatic invasion at diagnosis (28%).…”
Section: Discussionsupporting
confidence: 91%
“…Xiang et al reported in their research that 44.9% of MH-NENs originated from pancreas, 65.4% of cases present synchronous liver metastasis, 82.5% of cases had over 50% estimated liver involvement and 11.1% of cases present extrahepatic invasion [27] . As a result, our estimated 3-year OS for MH-NENs secondary to GEP-NENs was 45.6%, which was a little worse than that of previous studies [26,27] , probably due to the stricter inclusive criteria that MH-NENs in the present study was just secondary to gastroentero-pancreatic system, rather than other metastatic sites of NENs.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…[ 9 ] Tumors range in size from 0.4 to 19 cm (mean 6.84 ± 4.29 cm). [ 10 ] In our patient, the tumor measured 13 × 7 × 6 cm and involved the right 3 lobes of the liver. Routine histopathological examination using hematoxylin-eosin stains shows an insular, nested, trabecular or mixed cellular growth pattern, although this is a nonspecific finding.…”
Section: Discussionmentioning
confidence: 86%
“…Routine histopathological examination using hematoxylin-eosin stains shows an insular, nested, trabecular or mixed cellular growth pattern, although this is a nonspecific finding. [ 11 ] Lv et al [ 10 ] performed a retrospective study of the clinicopathological characteristics of 81 PHNETs and metastatic hepatic NETs and showed that patients with PHNETs demonstrated an aggressive clinical presentation. The hard texture of the tumor, multifocality of tumors, and the immunohistochemical expression of neuron-specific enolase and Syn were independent predictive factors.…”
Section: Discussionmentioning
confidence: 99%